The determinants of unemployment rate in Malaysia / Nurul Farhanah Abdul Rahman - Abdul Rahman, Nurul Farhanah (Faculty of Business and Management, 2020)
This study sought to explores the determinant factors affecting unemployment rate in Malaysia over the period of 1988 until 2018. The data series of variable Population (POPU), Labor Force (LF), Inflation Rate (IR), Gross Domestic Product (GDP) and Foreign Direct Investment (FDI) are to measure their relationship with Unemployment Rate (UR) using time series analysis. Moreover, this study attempts to examine the best model using Multiple Linear Regressions (MLR). The findings indicate that there is a significant negative relationship between Population (POPU) and Unemployment Rate (UR). There is also a insignificant negative relationship between Labor Force (LF) and Unemployment Rate (UR). However, study indicates that the is no causality relationship between Inflation Rate (IR) and Unemployment Rate. Other than that, the study found that there is significant negative relationship between Gross Domestic Product (GDP) and Unemployment Rate. Lastly, study indicates that there is insignificantly positive relationship between Foreign Direct Investment (FDI) and Unemployment Rate.